Impacts of Whale-Watching on the Short-Term Behavior of Fin Whales (Balaenoptera physalus) in a Marine Protected Area in the Southeastern Pacific - Santos-Carvallo, Macarena; Barilari, Fernanda; Pérez-Alvarez, María José; Gutiérrez, Laura; Pavez, Guido; Araya, Héctor; Anguita, Cristobal; Cerda, Claudia; Sepúlveda, Maritza (Frontiers in Marine Science, 2021)
Whale-watching (WW) is an activity which has been increasing worldwide due to the great interest of tourists and the economic benefits it provides to local communities. However, it has been reported that this activity affects the behavioral patterns of some cetaceans, although for some species such as the fin whale (Balaenoptera physalus) this has not been extensively studied. To identify the effects of WW on the behavioral patterns of this species, we studied its travelling and resting behaviors in a locality of north-central Chile from 2015 to 2018. Using a theodolite, we calculated the response variables of swim speed, directness index and re-orientation for each behavior. We used the number of WW boats and the WW scenarios of “before”, “during” and “after” the presence of boats as possible factors to explain the differences in the response variables of the whales, along with the factors of year, month, group size and distance from the observation point. Reorientation increased significantly and the directness index decreased significantly for both travelling and resting behaviors from “before” to “during” WW scenarios, indicating more erratic and sinuous movements in the presence of boats. These changes in movement patterns are a commonly reported evasion response of cetaceans to the presence of WW boats. For travelling behavior, the swimming speed significantly increased, and trends showed increased reorientation and a decrease in the directness index in the "after" WW scenario, which suggests perturbation of the whales potentially associated with the speed and the direction in which the boats left. During resting behavior, the trajectories of the fin whales became straighter (decrease in reorientation) as the number of boats increased, thus evasion (more erratic and sinuous movements) is a behavior used less by fin whales as the number of boats increases. Notwithstanding the fact that tourism development in the study area is small in scale, we found that WW generates adverse effects that are reflected in changes in the whales’ movement patterns. This kind of information is valuable to the adjustment and/or design of management strategies for the species, which is fundamental for WW continue to be a sustainable activity.